The effect of ICT usage on economic growth in the MENA region: Does the level of education matter? - Mohammed Abu Alfoul; Ibrahim N. Khatatbeh; Ayman Hassan Bazhair (Economies, 2024)
This paper examines the effect of information and communication technology (ICT) usage on economic growth in the Middle East and North Africa (MENA) region, with a focus on how education levels modulate this relationship. Covering data from 2000 to 2020 and employing a panel ARDL model for analysis, this research finds that, while ICT is prevalent across MENA, its impact on economic growth is negative. Furthermore, it reveals that education plays a crucial role in determining ICT's effectiveness on economic growth. However, the positive impact of education is overshadowed by the adverse effects of brain drain, which negates the potential benefits ICT could have on the economy. This study highlights the importance for MENA policymakers to address the brain drain issue to enhance the positive impact of ICT on economic growth, suggesting the need for strategies that leverage both ICT and education to effectively foster economic development.
Keywords: I25; O15; O33; 330; ICT; economic growth; education level; MENA region